Development of a Puzzle-Based Memory Game Learning Media to Improve Memorization Ability in the Shorof Subject for Grade 5 Students at SD IT Al Furqon - Siti Juliana (PGMI, STAI Miftahul Ula Nganjuk, 2025)
The development of puzzle-based memory game learning media for Grade 5 students at SD IT Al Furqon is based on a phenomenon observed at the school, namely the suboptimal use of learning media. This condition occurs because teachers tend to focus more on classroom management, and the learning process still relies heavily on assignments, resulting in teachers utilizing the surrounding environment as the primary learning medium. The objectives of this study are: (1) to describe the Research and Development (R&D) process in developing memory game learning media for the Shorof subject for Grade 5 students at SD IT Al Furqon; and (2) to describe the effectiveness of using memory game learning media in the Shorof subject for Grade 5 students at SD IT Al Furqon. The type of research used is Research and Development (R&D). According to Sugiyono, R&D is a research method aimed at producing specific products and testing their effectiveness. The development and research stages were adapted from Thiagarajan’s 4-D development model, which consists of: (1) the Define stage, including initial analysis, learner analysis, concept analysis, task analysis, and formulation of learning objectives; (2) the Design stage, including test preparation, media selection, and format selection; (3) the Develop stage, including expert validation, limited trials, and further trials; and (4) the Disseminate stage. The subsequent stages involved product trial design, trial subjects, and product revisions, including revisions by material experts and media experts. The results of the validation showed that the developed memory game media obtained an average percentage score of 96.3% from media experts, categorized as “very feasible for use.” Material experts provided an average percentage score of 89%, also categorized as “very feasible.” The overall average feasibility score was 92.7%, indicating that the media is suitable for use. Furthermore, educator responses yielded an average percentage of 92% with a “very feasible” category, while student responses showed an average percentage of 89.1%, also categorized as “very feasible.” In addition, the results of the pretest and posttest analysis showed an N-gain score of 0.71 or 71.85%. These results indicate that the developed product falls into the “high” category and demonstrates an “effective” level of effectiveness.